Mycelial inhibition of Trichoderma spp. (Hypocreaceae) isolated from the cultivation of Pleurotus ostreatus (Pleurotaceae) with an extract of Pycnoporus sp. (Polyporaceae) - Talavera Ortiz, Anaid (2020)
Background and Aims: The production of edible fungi is affected by bacterial, fungal and viral diseases, which very often cause large losses. In the production of mushrooms of the genus Pleurotus, the fungi of Trichoderma spp. represent a serious problem of contamination and although there are some chemical com-pounds that control the infection, they are not entirely safe for human consumption. As a consequence, alternatives are being searched for through biotechnol-ogy, such as the one presented in this paper.Methods: Strains of fungi of the genus Trichoderma were isolated from the substrate where Pleurotus ostreatus was being cultivated. These were identified morphologically and molecularly, followed by tests to inhibit the growth of Trichoderma strains in both agar and wheat straw, using a cetonic extract of the dehydrated fruiting body of Pycnoporus sp.Key results: Two strains of Trichoderma (T. pleuroti and T. atrobrunneum, belonging to the clade of T. harzianum) were isolated from infected substrate obtained in production modules of Pleurotus ostreatus located in Tlaquitenango and Cuernavaca, in the state of Morelos, Mexico. The effect of a cetonic extract of the fruiting body of Pycnoporus sp. on the mycelial growth of the isolated strains of Trichoderma was also evaluated, observing decrease in mycelial growth rate in Petri dish up to 72% and on lignocellulosic substrate both mycelial growth and sporulation were delayed up to 10 days. Conclusions: The extract of Pycnoporus sp. could be an alternative to control the infection by Trichoderma spp. in mushroom cultures of the genus Pleurotus.